PENGARUH METODE EMPAT TAHAP STEINBERG BERBANTUAN MEDIA ULAR TANGGA TERHADAP KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS I SEKOLAH DASAR - Mega Rosafina; Neneng Sri Wulan; Hisny Fajrussalam (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2025)
This study aimed to investigate two key aspects: 1) the influence of the Steinberg Four Stages method, supported by Snake and Ladder media, on the initial reading ability of first-grade students at SDIT Al-Bina, and 2) whether the initial reading ability of these students improved more significantly with this method and media compared to those using the Syllable method. This research was prompted by the observation that first-grade students at SDIT Al-Bina needed to improve their initial reading skills. The Steinberg Four-Stage method, combined with Snake and Ladder media, was explored as a potential solution to this issue, with the overall goal of enhancing these students' initial reading abilities. The study employed a Quasi-Experiment design with a Nonequivalent Control Group. The sample consisted of first-grade students from SDIT Al-Bina, divided into two groups of 28 students each: an experimental class and a control class. The findings indicate: 1) The Steinberg Four Stages method, aided by Snake and Ladder media, influenced students' initial reading ability by 72.9%. 2) There was a greater improvement in the initial reading ability of students who used the Steinberg Four Stages method with Snake and Ladder media compared to those who used the Syllable method. Keyword: Beginning Reading Ability, Steinberg's Four-Stage Method, Snake Ladder